Analysis of Self-Confidence in Adolescents with Anxiety at State Senior High School 5 Padang - Indah Novia Hendra; Tisnawati; Suhaimi (POLTEKKES KEMENKES PADANG, 2025)
In adolescents, physical problems often arise which are related to dissatisfaction with the condition of their body which does not match the desired ideal physique. Anxiety is often caused by lack of confidence in one's abilities and a lack of adjustment to a new atmosphere or environment. Anxiety in adolescents can be influenced by several factors, which one is self-confidence. Adolescents who lack self-confidence can be dangerous for mental health because adolescent tend to consider themselves failures or feel hopeless. This negative attitude can cause feelings of anxiety and depression in adolescent. The aim of this research was to determine the relationship between self-confidence and anxiety levels in adolescents at State Senior High School 5 Padang. Type of research Observational analytic with cross sectional design. Data collection from January to April 2024. The study population was all grade X students at State Senior High School 5 Padang in the 2023/2024 academic year totaling 431 people, a sample of 79 people using the proportional simple random sampling technique. Data collection using a questionnaire in the form of a questionnaire, data processing by editing, coding, entry, cleaning, tabulating. Analysis using the Chi square test (CI 95%). The results of the study, adolescents who experience anxiety (60.8%) and low self-confidence (54.4%). There is a significant relationship between self-confidence and anxiety levels p-value (0.000). It can be concluded that the higher the level of self-confidence, the less likely adolescents are to experience anxiety. is expected to help increase adolescent self-confidence and make a positive contribution to reducing their anxiety levels. This effort can be done by collaborating with health promotion officers at the relevant Health Center through health education that is carried out routinely and on schedule, especially aimed at adolescents in the area. It is hoped that the results of this study can increase the knowledge of adolescents regarding the importance of increasing self-confidence, so as to prevent anxiety in adolescents. Keyword : Anxiety; Confidence; Adolescent